(untitled) (Journal of EAHIL, 2017)
Deadline for applications: 16 January 2015 The EAHIL Executive Board is pleased to announce the availability of EAHIL-EBSCO Scholarships to be awarded to worthy individuals to attend the EAHIL Workshop in Edinburgh, Scotland, on 10-12 June 2015. The scholarships, which are partly sponsored by the generous support of EBSCO, will each be 500 euros maximum. The Board hopes to award a minimum of six scholarships, but reserves the right not to award the full number of scholarships if there are insufficient applications of the required standard.